A GIS-driven suitability analysis of crop resilience to climate change in Son La province, Vietnam - Truong, Tuyet Thi Anh; Almadrones Reyes, King Joshua; Kingsbury, Aaron (Agriculture and Natural Resources, 2024)
Importance of the work: This research addresses the critical impacts of climate change on land suitability for key crops in Son La province, Vietnam. Research gap: There is a lack of a comprehensive understanding of the effects of climate change on crop suitability in the mountainous regions of Vietnam. Objectives: To assess climate change impacts on crop suitability under current (1970–2000) and future (2081–2100) climate change scenarios. Materials and Methods: Using a weighted linear combination approach, environmental factors (annual temperature, accumulated precipitation, slope, soil type, humidity and depth) were modeled using the ESRI ArcMap software to generate suitability maps for fruit tree species (mango, longan and custard apple) and staple crops (maize and rice) under current conditions and under two future climate change scenarios—Shared Socioeconomic Pathways (SSPs) 1–2.6 (optimistic) and 3–7.0 (pessimistic). Results: Under current conditions (1970–2000), most land was marginally suitable for fruit trees and staple crops. Future climate scenarios projected a 27–60% reduction in unsuitable land for mango and longan, with increases in marginally and moderately suitable areas. Mango land gains amounted to 14 km² of moderately suitable land under the SSP1-2.6 scenario and 185 km² under the SSP3-7.0 scenario. Custard apple sites decreased by 65% for moderately suitable land under SSP1-2.6; however, there was a very large 3,175% increase under SSP3-7.0. For maize, unsuitable land decreased by 10%, with moderately suitable areas expanding to 3,691 km², while for paddy rice, unsuitable land reduced by 37–47%, with 76 km² of moderately suitable areas. Main finding: Future climate scenarios may improve land suitability for key crops, highlighting the need for national agricultural policies to incorporate adaptive strategies that leverage emerging opportunities for the mountainous regions.